FAKTOR - FAKTOR RISIKO TERJADINYA AKI (Acute Kidney Injury) PADA PASIEN DI ICU RSUP DR. SARDJITO ( Sepsis, Hipovolemia, Hipotensi, Operasi jantung, DM, Usia > 60 tahun, Obat nefrotoksik, Gagal jantung kongestif dan Pre eklampsi berat) - , Diva Musda Rusnadhi; , dr. Calcarina Fitriani RW, Sp.An, KIC. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Acute kidney injury (AKI) causes high mortality and often undiagnosed. AKI (Acute Kidney Injury) could be predicted using RIFLE (Risk- Injury-Failure-Loss-End Stage renal failure) criteria. Incidence of AKI among critical ill patients is quite high. AKI is a new terminology of acute renal failure. This terminology can explain all stages of renal injury from early stage up to renal failure. This terminology is used to recognize earlier renal disfunction. AKI used urine output and plasma creatinin as parameters of renal injury. Aim of this study to know that sepsis, hypovolemia, hypotension, cardiac surgery, diabetes mellitus (DM), age more than 60 years old, nefrotoxic agents, congestive heart failure, and severe eclampsy are risk factors of AKI of patients in ICU RSUP dr. Sardjito, Yogyakarta. Methode : Cohort retrospective study. Subjects of this study about 121 patients admitted to ICU RSUP dr. sardjito from January up to march 2013. All of the patients have complete data during in care at ICU. No congestive heart failure patient were recruited in this study. Result : This study shows that hypotension (RR 18,46, p value 0,0001), severe eclampsy (RR 15,85, p value 0,0001), and sepsis (RR 5,32, p value 0,001) are independent and strong risk factors for incidence of AKI in patients which in care at ICU RSUP dr Sardjito. Hypovolemia, nefrotoxic agents, and age more than 60 years old are also risk factors for AKI. Diabetes mellitus with no complication and cardiac surgery are not risk factors for AKI. Conclusion : Hypotension, severe eclampsy, and sepsis are independent and strong risk factors for incidence of AKI in patients which in care at ICU RSUP dr Sardjito. Hypovolemia, nefrotoxic agents, and age more than 60 years old are also risk factors for AKI. Diabetes mellitus with no complication and cardiac surgery are not risk factors for AKI.